2009
DOI: 10.1002/psc.1158
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase peptide synthesis using acetonitrile as a solvent in combination with PEG‐based resins

Abstract: This manuscript shows that ACN can be an excellent choice for the coupling of hindered amino acids as illustrated by the coupling of Fmoc-amino acids on free amino acids anchored on a BAL synthesis. Furthermore, ACN can be a good alternative for solid-phase peptide synthesis in the absence of DMF (washings, removal of Fmoc, and coupling).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 25 publications
0
55
0
Order By: Relevance
“…[34][35][36] To the best of our knowledge, 45 unmodified ACP decapeptide has frequently beenused fortestingnew protocols. 17,[37][38][39] In this study, two Aib residuesreplaced the two consecutive Ala residues in the normal ACP decapeptide in order to make it a more difficult sequence and as a result allow a clear observation of the effect of solvent 50 on the synthesis of a long peptide.Decapeptide 10 was manually assembledstepwise on Fmoc-RinkAmide-AM-ChemMatrix-resin by means of a 1-h coupling (except Aib-Aib where a 2-h double coupling was applied) with an excess of 3 equivalents of Fmocamino acid/additive/carbodiimide. 55 In all cases, both THF and ACN yielded better purity of the decapeptide 10 than DMF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] To the best of our knowledge, 45 unmodified ACP decapeptide has frequently beenused fortestingnew protocols. 17,[37][38][39] In this study, two Aib residuesreplaced the two consecutive Ala residues in the normal ACP decapeptide in order to make it a more difficult sequence and as a result allow a clear observation of the effect of solvent 50 on the synthesis of a long peptide.Decapeptide 10 was manually assembledstepwise on Fmoc-RinkAmide-AM-ChemMatrix-resin by means of a 1-h coupling (except Aib-Aib where a 2-h double coupling was applied) with an excess of 3 equivalents of Fmocamino acid/additive/carbodiimide. 55 In all cases, both THF and ACN yielded better purity of the decapeptide 10 than DMF.…”
Section: Resultsmentioning
confidence: 99%
“…16 Several years ago, some of the authors of the present study 70 demonstrated that ACN,in combination with a totally polyethyleneglycol-based resin, is agood alternative to DMF and NMP. 17 The capacity of solvents to swell the resin is considered one of the main requirements of solvents used in solidphasepeptide synthesis. In general, polyethlyeneglycol-based 75 resin swells better than polystyrene in response to all solvents.…”
Section: Introductionmentioning
confidence: 99%
“…22,26,28 This reagent was evaluated for its efficiency in SPPS using the Aib-enkephalin pentapeptide model (H-Tyr-Aib-Aib-Phe-Leu-NH 2 ). 28,29 This model is a modified version of the Leuenkephalin pentapeptide, 31 where two glycine residues are replaced by the hindered α,α-disubstituted amino acid (Aib). This modification leads to difficult coupling of the second Aib residue and therefore the formation of des-Aib tetrapeptide (H-Tyr-AibPhe-Leu-NH 2 ) as a major side-product.…”
Section: Scheme 1 Preparation Of Oxyma-tmentioning
confidence: 99%
“…This approach was first reported by Acosta et al who investigated the use of acetonitrile as a replacement for DMF in SPPS couplings [30,31]. Whilst acetonitrile is not often considered as a green solvent, it can be regarded as a less problematic dipolar aprotic solvent, when compared to DMF [5].…”
Section: Alternative Organic Solventsmentioning
confidence: 99%
“…Whilst acetonitrile was unable to swell conventional PS-based resins it could adequately swell PEG-based resins. Acosta et al then demonstrated the suitability of acetonitrile for SPPS in the preparation of the test peptides Leu-enkephalinamide and acyl carrier protein (ACP 65-74) (H-Val-Gln-Ala-Ala-Ile-Asp-Tyr-Ile-Asn-Gly-NH 2 ), upon PEG-based resins in excellent crude purity [30]. Subsequent reports from Albericio and co-workers have continued along the same theme of using less problematic alternatives to DMF for SPPS couplings, with the use of acetonitrile explored in more detail, along with THF, 2-MeTHF and CPME [32,33].…”
Section: Alternative Organic Solventsmentioning
confidence: 99%